Gastric Emptying in Migraine: A Comparison With Functional Dyspepsia - Yu, Yeon Hwa (Korean Society of Neurogastroenterology and Motility, 2012)
BACKGROUND/AIMS: Gastric stasis in migraineurs remains controversial. The aim of this study is to investigate gastric emptying (GE) time, and any associations between GE parameters and dyspeptic symptoms among patients with functional dyspepsia (FD) and migraine without any gastrointestinal symptoms during the interictal period. METHODS: We enrolled 27 migraine patients, 32 FD patients and 12 healthy people as controls, and performed GE scintigraphy as gastric function test. Gastrointestinal symptoms were evaluated in the FD and migraine. RESULTS: The age-adjusted mean gastric half-emptying time in FD (125.51 ± 52.55 minutes) patients was longer than in migraineurs (100.82 ± 23.94 minutes, P = 0.035) and controls (95.25 ± 23.29 minutes, P = 0.021). The percentage of gastric retention was higher in FD than in migraine. However, migraineurs did not show an obvious delayed gastric emptying or an increase of gastric retention when compared to the normal controls. The association between each dyspeptic symptom and GE parameters was not significant, but postprandial fullness and early satiety showed a tendency of delayed GE. In migraineurs, GE time did not show significant association with nausea and vomiting during interictal periods. CONCLUSIONS: Delayed GE does not appear to be a mechanism that patients with FD and migraine have in common. Migraineurs without dyspepsia during interictal period had normal GE, and further study for association with FD should be investigated.